Hypoxia-Induced Upregulation of lncRNA ELFN1-AS1 Promotes Colon Cancer Growth and Metastasis Through Targeting TRIM14 via Sponging miR-191-5p - Jing, Xu; Du, Lutao; Shi, Shuang; Niu, Aijun; Wu, Jing; Wang, Yunshan; Wang, Chuanxin (Frontiers in Pharmacology, 2022)
Hypoxia is identified as one of the microenvironmental features of most solid tumors and is involved in tumor progression. In the present research, we demonstrate that lncRNA extracellular leucine rich repeat and fibronectin type III domain-containing 1-antisense RNA 1 (ELFN1-AS1) is upregulated by hypoxia in colon cancer cells. Knockdown of ELFN1-AS1 in hypoxic colon cancer cells can reduce cell proliferation and restore the invasion to non-hypoxic levels. Fluorescence in situ hybridization results show that ELFN1-AS1 is distributed in the cytoplasm of colon cancer cells, so we further analyze the potential targets for ELFN1-AS1 as a competing endogenous RNA (ceRNA). MiR-191-5p contains a binding sequence with ELFN1-AS1 and is downregulated by ELFN1-AS1 in colon cancer cells. Then, there is a binding site between miR-191-5p and the 3′ untranslated region of tripartite motif TRIM 14 (TRIM14). The expression of TRIM14 is inhibited by ELFN1-AS1 siRNA or miR-191-5p mimics in LoVo and HT29 cells. The treatment of the miR-191-5p inhibitor in ELFN1-AS1 knockdown cells can significantly increase cell proliferation and invasion ability. Overexpression of TRIM14 in miR-191-5p-mimic-treated cells can rescue the inhibition of proliferation and invasion caused by miR-191-5p mimics. In conclusion, ELFN1-AS1 operates as a downstream target of hypoxia, promotes proliferation and invasion, and inhibits apoptosis through upregulating TRIM14 by sponging miR-191-5p in the colon cancer cells. Our results enrich our understanding of colon cancer progression and provide potential targets for clinical treatment of colon cancer.